1999
DOI: 10.1080/13596749900200060
|View full text |Cite
|
Sign up to set email alerts
|

Invisibility, perceptions and image: mapping the career choice landscape

Abstract: The education and training market, particularly for 16 year olds, is highly competitive and an understanding of how young people make decisions about careers and how that affects and interacts with choice of further and higher education pathways is a crucially important issue. The complexity of the decision-making process has been largely under-estimated in favour of an oversimplification of the economically rational view of choice. However, young people make choices which have an impact on the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…In contrast, Lehmann (2007b) showed how persistent habitus dislocation led working-class university students to drop out of university. Foskett and Hemsley-Brown (1999) argue that young people's perceptions of careers are a complex mix of their own experiences, images conveyed through adults, and derived images conveyed by the media. Media images of careers, perhaps, are even more important for working-class youth with high ambitions as they offer (generally distorted) windows into a world of professional employment to which they have few other sources of access.…”
Section: Transitions Decisions and Social Classmentioning
confidence: 99%
“…In contrast, Lehmann (2007b) showed how persistent habitus dislocation led working-class university students to drop out of university. Foskett and Hemsley-Brown (1999) argue that young people's perceptions of careers are a complex mix of their own experiences, images conveyed through adults, and derived images conveyed by the media. Media images of careers, perhaps, are even more important for working-class youth with high ambitions as they offer (generally distorted) windows into a world of professional employment to which they have few other sources of access.…”
Section: Transitions Decisions and Social Classmentioning
confidence: 99%
“…Exposure is a student's contact with a career resulting from his or her unique set of circumstances (Foskett & Hemsley-Brown, 1999), and refers to information the student encounters by chance. Racial and ethnic culture and economic class (Simpkins, Davis-Kean, & Eccles, 2006) may limit youths' exposure to and pursuit of higher education and professional careers (Lucas & Buzzanell, 2004).…”
Section: Framework and Personal Factorsmentioning
confidence: 99%
“…Foskett and Hemsley-Brown (2001) found that students placed a greater premium on 'experiential information' (including face-to-face contact with outside visitors such as employers) than paper-based information. Foskett and Hemsley-Brown (1999) also observed that whereas guidance interviews tend to explore the personal choices learners bring to the…”
Section: Comparing Interventionsmentioning
confidence: 99%